Management of displaced transverse fractures of the patella using tension band wiring with or without circumferential cerclage wiring: A comparative study - Lone, Zubair A.; Mohd, John; Mohd, John; Beigh, Imtiyaz A.; Beigh, Imtiyaz A.; Bhat, Tanveer A.; Bhat, Tanveer A.; Afzal, Tahir M.; Afzal, Tahir M.; Gupta, Anil; Gupta, Anil (International Journal of Research in Medical Sciences, 2019)
Background: Transverse fractures of body of the patella are by far the most common fractures of this bone. Surgical fixation is the recommended treatment in displaced fractures with extensor lag. Although, tension band wiring (TBW) technique is the gold standard for these fractures, few surgeons recommend augmentation with circumferential cerclage wiring to improve the strength of the fixation. We compared the results of the internal fixation of displaced transverse fractures of the patella using TBW and circumferential cerclage wiring with those treated with TBW alone. Methods: We treated 54 displaced transverse fractures of the patella at our institution. We segregated the patients into two groups: Group 1 (n=23) included fractures treated with tension band wiring (TBW) along with augmented circumferential cerclage wiring while as Group 2 (n=31) included fractures treated by TBW alone. Outcome was studied, graded and compared on the basis of knee pain, knee stiffness, quadriceps wasting, loss of flexion and loss of extension. Results: 73.90% patients among group 1 and 70.96% among group 2 showed excellent to good results (P value < 0.1). Fixation failure and need for revision surgery among group 1 and group 2 was found to be 8.69% and 9.67%, respectively (P value < 0.6). Infections and non union occurred among 4.34% patients in group 1 whereas in group 2 it was 6.45% of the patients who encountered the same (P value < 0.6). Conclusions: The use of circumferential cerclage wiring along with tension band wiring for displaced transverse fractures of patella seems to have no added advantage over fixation with tension band wiring alone. Keywords: Patella fracture, Tension band wiring, cerclage wiring